Procedure For Transforming Financial Statements On The Basis Of International Standards - Azizova Zilola Lochinovna (Peerian Journals Publishing, 2023)
The article defines the procedure of making and converting national accounts based on international reporting standards. In addition to provides detailed information about the difference between existing reporting forms from international financial reporting and the procedure of preparation.
Keywords: Financial report; national accounting standards; international accounting standards